Geomorphological mapping as an instrument for coastal areas planning: Thoughts from the whales coast region - Bahia - Brazil. - Souza, Sirius Oliveira; Lupinacci, Cenira Maria [UNESP]; de Oliveira, Regina Célia (Revista Brasileira de Geomorfologia, 2021)
This study aimed to discuss the coastal geomorphological dynamics and their implications for the adequate management. Thus, from the geomorphological mapping, the morphodynamic processes that characterize the relief compartments are pointed out and important aspects to proper planning of these terrains. The study area covers the municipalities of the Costa das Baleias Region (south coast of Bahia State), geomorphologically marked by Coastal Tablelands. The lack of studies on this scenario, very frequent on the Brazilian coast, justified our choice, in order to contribute effectively to the study of these environments. The geomorphological map was prepared based on aerial photographs with a scale of 1: 25,000 and field data. The results showed the concentration of erosional forms on the exposed slopes to the east/southeast tablelands. In addition to the trays, there are alluvial terraces and quaternary coastal plains that demonstrate morphologies still in the sedimentation phase, a fact that determines limitations for use due to the instability of the terrain and the occurrence of periodic flooding. Thus, this work intends to subsidize planning proposals for the land use and occupation of Coastal Tablelands.
A Cartografia Geomorfológica enquanto instrumento para o planejamento em áreas litorâneas: Considerações a partir da região Costa das Baleias - Bahia - Brasil.
Keywords: Compartmentation; Digital stereoscopy; Geomorphological mapping